1996
DOI: 10.1007/bf00029261
|View full text |Cite
|
Sign up to set email alerts
|

Species relationships in the subgenus Ceratotropis (genus Vigna) as revealed by RAPD analysis

Abstract: The genetic variation among 23 accessions of 5 species in the subgenus Ceratotropis, genus Vigna, were investigated by random amplified polymorphic DNA (RAPD) analysis . A total of 404 fragments amplified with 24 primers were scored and analyzed by cluster analysis . The accessions used were separated into two main groups with an average of 70% differences . Within the main groups, five subgroups were recognized, which are in complete agreement with taxonomic species . Wild forms were always grouped with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 18 publications
7
35
0
1
Order By: Relevance
“…Analysis of the rDNA genes support claims that wild cowpea and mungbean are progenytors of the present day cultivated cowpea and mungbean respectively. Similarly, the analysis of the rDNA genes reveals the presence of homologous genes in Vigna radiata and Vigna mungo corroborating previous studies by Kaga et al (1996) and Goel et al (2001).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Analysis of the rDNA genes support claims that wild cowpea and mungbean are progenytors of the present day cultivated cowpea and mungbean respectively. Similarly, the analysis of the rDNA genes reveals the presence of homologous genes in Vigna radiata and Vigna mungo corroborating previous studies by Kaga et al (1996) and Goel et al (2001).…”
Section: Resultssupporting
confidence: 76%
“…The dendrogram (Figure 7) also reveals a close relationship between Vigna radiata and Vigna mungo which corroborates similar findings of Kaga et al (1996) and Goel et al (2001). Both V radiata and V mungo are in the subgenera Ceratotropis also known as Asian genus Vigna and their germplasms are useful for making crosses within the species of Vigna.…”
Section: Phylogenetic Analysissupporting
confidence: 72%
“…Gepts (1993) suggested that molecular markers provide more useful information than morphological markers for studies on the domestication and evolution of plants. Random amplified polymorphic DNA markers (RAPD) were used in studies conducted by Cisneros and Quiros (1995) on triploid potatoes (Solanun chaucha), by Demeke and Adams (1994) on mustard and radish, by Sharma et al (1996) on lentils, by ReamonBĂĽttner et al (1996) on beets and by Kaga et al (1996) on the genus Vigna. Amplified fragment length polymorphism markers (AFLP) have been used in studies of genetic relatedness performed by Hill et al (1996), Cervera et al (1996) and Sharma et al (1996).…”
Section: Introductionmentioning
confidence: 99%
“…Plant Breed. Genet., 9 (4): 238-246, 2015 for genome mapping experiments (Kaga et al, 1996). Genotyping of different species is necessary for characterization of different accessions of crop germplasm, testing varietal purity and registration of newly developed cultivars (Chowdhury et al, 2002).…”
Section: Introductionmentioning
confidence: 99%